Analisis Faktor-faktor yang Mempengaruhi Perilaku Konsumen dalam Pengambilan Keputusan Pembelian White Coffe - Khasan, Umar (Badan Penelitian dan Pengembangan Provinsi Jawa Timur, 2018)
The Goals of this research are analyze factors affect to purchase products White Coffee. Research was carried out in Hypermart Bangkalan. Sample was taken by accidentl sampling method. Data were analyzed by qualitative diskriptif. The result of factors affect the purchase decision of White Coffee are culture.